Inhibition of Glycogen Synthase Kinase 3β (GSK3β) Decreases Inflammatory Responses in Brain Endothelial Cells - Ramirez, Servio H. (American Society for Investigative Pathology, 2010)
Immune mediators and leukocyte engagement of brain microvascular endothelial cells (BMVECs) contribute to blood–brain barrier impairment during neuroinflammation. Glycogen synthase kinase 3β (GSK3β) was recently identified as a potent regulator of immune responses in in vitro systems and animal models. However, the role of GSK3β in regulation of immune endothelial functions remains undetermined. Here we evaluated the effect of GSK3β inhibition on the regulation of inflammatory responses in BMVECs. A focused PCR gene array of 84 genes was performed to identify the cytokine and chemokine gene expression profile in tumor necrosis factor (TNF) α-stimulated BMVECs after GSK3β inactivation by specific inhibitors. Fifteen of 39 genes induced by TNFα stimulation were down-regulated after GSK3β inhibition. Genes known to contribute to neuroinflammation that were most negatively affected by GSK3β inactivation included IP-10/CXCL10, MCP-1/CCL2, IL-8/CXCL8, RANTES/CCL5, and Groα/CXCL1. GSK3β suppression resulted in diminished secretion of these proinflammatory mediators by inflamed BMVECs detected by ELISA. GSK3β inhibition in BMVECs reduced adhesion molecule expression as well as monocyte adhesion to and migration across cytokine stimulated BMVEC monolayers. Interactions of monocytes with TNFα-activated BMVECs led to barrier disruption, and GSK3β suppression in the endothelium restored barrier integrity. GSK3β inhibition in vivo substantially decreased leukocyte adhesion to brain endothelium under inflammatory conditions. In summary, inhibition of GSK3β emerges as an important target for stabilization of the blood–brain barrier in neuroinflammation.